The Effect of Cross-Linking with Citric Acid on the Properties of Agar/Fish Gelatin Films - Uranga, Jone (Polymers (Basel), 2020)
The aim of this work was to assess the effect of fish gelatin–citric acid nucleophilic substitution and agar–citric acid esterification reactions on the properties of agar/fish gelatin films. Since temperature is an important cross-linking parameter, films were treated at 90 °C and 105 °C and film properties were compared to those of non-cured films. It was observed that temperature favored the aforementioned reactions, which induced physical and morphological changes. In this regard, darker films with a rougher surface were obtained for the films with a higher cross-linking degree. While mechanical properties were slightly modified, the barrier properties were enhanced due to the reactions that occurred. Therefore, these agar/fish gelatin films cross-linked through two different reactions can be considered to be promising materials as active films for different purposes, such as active packaging or pharmaceutical applications.